Refrigeração evaporativa por aspersão em telhas de fibrocimento: estudo teórico e experimental - Roriz, Victor Figueiredo (2007)
This research focuses the evaporative cooling by water aspersion on wavy cement fiber tiles in the city of São Carlos, SP, seeking to use it to reduce the buildings heat gains. A theoretical model was developed, based on classic equations of fluids mechanic, applied to iterative calculations of heat flows on the tile superior surface, considered as control surface. In the work development, this model was progressively adjusted to experimental data obtained in a test cell, exposed to the local climatic conditions, with the monitoring of superficial temperatures of both faces in two tiles, one maintained dry and other under intermittent aspersion of water. The research results indicated that, despite of still being susceptible to improvement, the theoretical model already presents quite satisfactory approach with the measured data. Applying a statistical adjustment to the proposed model of iterative heat flows calculation, it was obtained a correlation coefficient between measured and estimated temperatures of 0,999 and a standard deviation of 0,35 ºC. During the experiments, the average evaporative heat flow was 409 W/m2. Theaverage water volume evaporated was 0,7 l/(m².h), corresponding to an average difference of temperatures among the compared tiles of 5,12 K, for the daylight period. Due to the growing need of energy consumption reduction, this procedure seems to be a good option to reduce buildings thermal load, if compared to conventional air conditioning systems